Manajemen Ekstrakurikuler Komputer dalam Meningkatkan Keterampilan Siswa di Sekolah Dasar Negeri Karangrejo 03 - Devi Dewi Hajar; Nur Ittihadatul Ummah (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the management of computer extracurricular activities at SDN Karangrejo 03 in improving students' skills in the field of technology. The approach used is qualitative with observation, interview, and documentation methods. The results of the study indicate that computer extracurricular activities are planned systematically through identifying student needs, scheduling activities, and providing facilities. The organization involves supervising teachers and the formation of study groups based on student abilities. The mobilization process is carried out by providing motivation through awards, interactive learning materials, and collaboration. Routine supervision by the principal and teachers ensures implementation according to plan. This activity not only improves students' technical skills but also critical and creative thinking skills, preparing them to face the challenges of the digital era. This study concludes that effective management in computer extracurricular activities plays an important role in the development of students' overall skills.